2019
DOI: 10.13170/depik.8.3.12090
|View full text |Cite
|
Sign up to set email alerts
|

Penambahan mineral kalsium dari cangkang kepiting bakau (Scylla serrata) pada pakan terhadap pertumbuhan dan kelangsungan hidup udang galah (Macrobrachium rosenbergii)

Abstract: Abstract. Mud crab shell is one of the most fisheries waste can be utilized as calcium source because it contains lots of calcium carbonat. Utilizing of crab shells flour in fed is important applied as calcium supplements to freshwater prawn. The purpose of this research is to knows the effects of calcium addition from mud crab shells on fed to increase the growth rate, survival rate and moulting frequency freshwater prawn. The research has been done during 70 days in fisheris Laboratory, Abulyatama University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
3
0
7
Order By: Relevance
“…(2) the rajungan crab shells. These results also showed that the calcium content of bakau crab shells with a calcium content of 53.7-78.4 % (Fajri et al, 2019) was higher than the calcium content of rajungan crab shells, which was around 6.81-26.82 % (Hastuti et al, 2012).…”
Section: Calcium Extractionmentioning
confidence: 93%
“…(2) the rajungan crab shells. These results also showed that the calcium content of bakau crab shells with a calcium content of 53.7-78.4 % (Fajri et al, 2019) was higher than the calcium content of rajungan crab shells, which was around 6.81-26.82 % (Hastuti et al, 2012).…”
Section: Calcium Extractionmentioning
confidence: 93%
“…Berbagai penelitian terkait keistemewaan komposisi kimia cangkang tiram telah dilakukan (Chilakala et al, 2019;Handayani & Syahputra, 2017;Silva et al, 2019) bahkan penelitian mengenai pendayagunaan cangkang kerang-kerangan sebagai sumber kalsium bagi ikan telah dikembangkan. Udang yang diberi tambahan kalsium sebagai suplemen dari cangkang tiram dapat meningkatkan frekuensi molting, kelangsungan hidup serta pertumbuhan (Asmaini et al 2020;Fajri, et al 2019;Fitriana et al 2019;Handayani et al 2019;Handayani & Syahputra, 2018;Restari et al 2019;Zufadhillah et al 2018). Kekuatan cangkang telur pada unggas dipengaruhi oleh kecukupan kalsium.…”
Section: Pendahuluanunclassified
“…Pemanasan pada suhu tinggi 900 0 C selama 2 jam pada pembuatan tepung kepiting bertujuan untuk melakukan kalsinasi tepung yang dihasilkan (Fajri et al, 2019…”
Section: Penulis Korespondensiunclassified